2022
DOI: 10.7554/elife.80556
|View full text |Cite
|
Sign up to set email alerts
|

An international observational study to assess the impact of the Omicron variant emergence on the clinical epidemiology of COVID-19 in hospitalised patients

Abstract: Background:Whilst timely clinical characterisation of infections caused by novel SARS-CoV-2 variants is necessary for evidence-based policy response, individual-level data on infecting variants are typically only available for a minority of patients and settings.Methods:Here, we propose an innovative approach to study changes in COVID-19 hospital presentation and outcomes after the Omicron variant emergence using publicly available population-level data on variant relative frequency to infer SARS-CoV-2 variant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…in any of the omicron cases of our cohort 16 . Our observations are in concordance with clinical data associating an omicron infection with a milder disease course and low lethality 12,17,18 . Thus, the extent of lung injury is still an important denominator for patients’ prognosis and the clinical course of COVID‐19.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…in any of the omicron cases of our cohort 16 . Our observations are in concordance with clinical data associating an omicron infection with a milder disease course and low lethality 12,17,18 . Thus, the extent of lung injury is still an important denominator for patients’ prognosis and the clinical course of COVID‐19.…”
Section: Discussionsupporting
confidence: 88%
“…16 Our observations are in concordance with clinical data associating an omicron infection with a milder disease course and low lethality. 12,17,18 Thus, the extent of lung injury is still an important denominator for patients' prognosis and the clinical course of COVID-19. However, besides attenuation of viral pathogenicity, vaccination or resolved infection improved the specific immune status of the population, and improvement in disease management may also be an important factor for a better outcome of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical investigations revealed a decreased pathogenicity of BA.1 and BA.2 when compared to previous VOCs, 10 , 11 , 12 , 13 , 14 which are in agreement with previous in vitro and in vivo studies reported from us and others. 4 , 8 , 15 , 16 However, clinical severity of BA.5 and its related sublineages remain incompletely understood.…”
Section: Introductionsupporting
confidence: 92%
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 Subsequent Omicron subvariants emerged in waves, with a subvariant replacing the previous one every few months. We and others have evaluated the virological features, replication, and pathogenicity of these dominant Omicron subvariants, including BA.1, 6 , 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 42 , 43 , 44 , 45 , 46 BA.2, 23 , 24 , 25 , 26 , 35 , 47 , 48 , 49 and BA.5. 27 , 28 , 36 , 40 , 41 , 50 , 51 , 52 , 53 , 54 , 55 , 56 More recently, the emerged post-BA.2/5 subvariants were unable to successfully outcompete other subvariants to become the dominant Omicron lineage worldwide, leading to the cocirculation of multiple Omicron subvariants.…”
Section: Discussionmentioning
confidence: 99%